Diagnostic value of the cytogenetic analysis - diffuse large B cell lymphoma case with atypical localization - Pieńkowska-Grela, Barbara; Grygalewicz, Beata; Sikora, Krzysztof; Woroniecka, Renata (Contemporary Oncology/Współczesna Onkologia, 2002)
A 39-year-old patient, edycja suspected of testicular cancer was admitted to the Urology Clinic and left - sided inguinal orchidectomy was performed. The preliminary diagnosis of seminoma testis sinistri, grade I was estabished. Cytogenetic study was performed using subsequent conventional G-band analysis and fluorescent in situ hybridization (FISH) method using specific DNA probes. Analysis of G-banded metaphases revealed a hypotetraploid chromosome complement with many non-random chromosome aberrations. Those changes mainly comprised 1, 6, 18 and X chromosomes. Aberrations of 12p material were not detected, especially isochromosome i(12p) was absent. The amplification of the short arm of the chromosome 12, especially as the i(12p) marker chromosome, has been found as a highly non-random chromosome abnormality associated with testicular germ cell tumors (TGCT). Amplification of 12p material is specific for all histological types of such tumors. In 80-90 per cent of cytogenetically analysed TGCT an overrepresentation of complete short arm of chromosome 12, as the i(12p) marker, has been frequently reported. Furthermore, studies using FISH methods have revealed that 12p aberrations occur in every i(12p)-negative TGCT. In such cases multiplicated 12p material has been found in markers substitutive for i(12p). In the current studied case, analysed cells showed multiplication of normal copy of chromosome 18 and some chromosomal markers, that involved chromosome 18 material. A huge amplification of chromosome 18 material was observed preliminarily in banding metaphases. That was also confirmed by FISH analysis. Chromosome 18 amplification is not specific for TGCT, but it is mostly characteristic for some subtypes of Non Hodgkin Lymphomas (NHL). The result of cytogenetic analysis brought the preliminary diagnosis in question. The second analysis of histological specimens and additionalimmunohistochemical and histochemical examination permitted to establish a final diagnosis as Diffuse Large B-Cell Lymphoma (DLBCL). Diffuse Large B-Cell Lymphoma is characterised by marked heterogeneity in phenotype and clinical behaviour. Cytogenetic studies that demonstrated chromosomal alteration in tumor cells is useful in the diagnosis and correct classification of Non Hodgkin's Lymphomas.